A Brief Talk on the Research of Regional Landscape Design Combining Nature and Humanism under Computer Background. Issue 3 (October 2020) - Gu, Xin
Abstract: The role of landscape design in urban construction has become more and more important, but at the same time of rapid urban development, the frequent destruction of traditional landscapes and cultural heritage is not uncommon. Nowadays, the public space landscape in many cities has become blind due to blind construction. The mediocrity loses its characteristics. Regional landscape design is based on the characteristics of the development of the times and the characteristics of regional natural and human conditions. It is proposed that the combination of design and regional should be adhered to in the regional landscape design. This article uses computer technology, integrates the natural and humanistic elements, studies the related issues of applying regional features in landscape design, and takes Hangzhou as an example to conduct practice and analysis. Practice shows that when the design complies with nature, it can better adapt to local conditions and create a benchmark landscape.